Development Of Integrative Food Waste Treatment And Lactic Acid Production - Macnister Gestney Langga, Anding (2022)
Food waste is a major problem that costs the global economy around 16,688 tons of food are produced every day in the economy, enough to feed 2.2 million people three times a day. Due to greenhouse gas emissions generated during food manufacturing and process, food waste also contributes to global warming and climate change. This food waste contains a high concentration of carbohydrates, lipids, proteins, nitrogen sources and vitamins. Food waste have been chosen as substrate in this study to extract become lactic acid. These days, food waste population becomes increasing day by day and this donate to problems in several part and no inconsistency into environment if this problem bot controlled correctly. In this study, 500 ml bottle act as the batch fermentation reactor was used and two fraction of food waste namely starchy fraction (white bread waste) and cellulosic fraction (fruit waste) was compared which food waste fraction could produce the higher yield. Furthermore, the duration of fermentation, temperature and initial pH for food waste fermentation were also confirmed in this study. Moreover, improvement of lactic acid production by adding a starter culture in food waste was also explored. All waste fractions and food waste were grinded separately in distilled deionized water to form food waste slurry (sterilized by autoclaving), initial pH adjusted to pH 7 and fermented was left at room temperature. The most efficient food waste based on yield of lactic acid was white bread waste. The most suitable fermentation time is 15 days and temperature are 36.4oC. The result of the Chemical Oxygen Demand (COD) and Biochemical Oxygen Demand (BOD) indicate the efficiency of the food waste treatment while the reading of the pH indicate the presence of the acid in the sample. The result indicated that both fraction of food waste has the presence of the lactic acid but in different concentration.